2012
DOI: 10.1097/mbc.0b013e32834cb35d
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of von Willebrand factor

Abstract: von Willebrand factor (VWF) is a long plasma protein that contains many domains and each domain has its own function. VWF exists in a multimeric form and performs varieties of functions in the human body, including thrombus formation and blood coagulation. The crystal structures of three subdomains are known, and, interestingly, all three domains share identical three-dimensional fold with α-β-α sandwiched model. VWF is directly associated with different types of von Willebrand disease. In this review, our aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 145 publications
4
31
0
1
Order By: Relevance
“…It functions as a mediator of platelet-endothelial/subendothelial adhesion to promote platelet aggregate formation, as well as a carrier for Factor VIII in the circulation [25]. In addition to its major role in hemostasis, VWF has been reported to participate in the immune response, inflammation, angiogenesis and cancer metastasis [68].…”
Section: Introductionmentioning
confidence: 99%
“…It functions as a mediator of platelet-endothelial/subendothelial adhesion to promote platelet aggregate formation, as well as a carrier for Factor VIII in the circulation [25]. In addition to its major role in hemostasis, VWF has been reported to participate in the immune response, inflammation, angiogenesis and cancer metastasis [68].…”
Section: Introductionmentioning
confidence: 99%
“…After 4 weeks, immunohistochemistry was used to assess the density and size of vascular structures with the delivery of saline, composites without IL‐10, or composites with IL‐10 and representative images are shown in Figure 10 A–C. Von Willebrand factor (vWF) is a glycoprotein produced by endothelial cells and is present in the lumen of vascular structures of all sizes, from capillaries to arterioles, whereas alpha‐smooth muscle actin (α‐SMA) is expressed by smooth muscle cells and is only present in more mature vasculature . Both vWF + and vWF + α‐SMA + vascular structures contribute to enhancing perfusion in the border zone region after MI.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Znf-containing proteins function in gene transcription, translation, mRNA trafficking, cytoskeleton organization, epithelial development, cell adhesion, protein folding, chromatin remodelling and zinc sensing [92]. We also found that NP_214882.1 and NP_215474.1 are showing similarity with von Willebrand factor with a type A domain, which is found to be responsible for various blood disorders [93][94][95]. Association of type A domain makes it liable to be involved in various significant activities such as cell adhesion and immune defense [96].…”
Section: Binding Proteinsmentioning
confidence: 94%